PERANCANGAN KURSI SANTAI DENGAN DESAIN STREAMLINE BERBAHAN DASAR ROTAN - Surya, Geggy Gamal (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
The development of increasingly advanced times we as humans expect the emergence of new things that are more practical and comfortable in their use and have more usability than previous products. This is also supported by the availability of supporting tools that are equipped with current technology for manufacturing and growing human needs for convenience. In general, lounge chairs are one of the furniture that are familiar to us everyday. Rattan is a very large source of foreign exchange for the country because Indonesia is one of the largest rattan producing countries in the world. Streamline architecture emphasizes curved shapes, long horizontal lines, and sometimes sea elements. In industrial design, it is used in railroad locomotives, telephones, toasters, buses, equipment, and other devices to give a subtle and modern impression.